Exploring Cultural Diversity in Indonesia: Models, Responses, and Multicultural Politics - Acim, Acim; Subagja, Dita Jelia; Afiani, Diva Ayu; Pratama, Georgy Rio; Al Kautsar, Fathan (Candidate: Jurnal Sains Politik, 2023)
Religiosity is a thing in which there are many differences that grow and emerge in social life, of course this diversity is a common thing, because it is certain thatthis diversity arises and develops so that humans can respect each other, and ofcourse so that community groups can live side by side without seeing anydifference. Of course, the challenge that must be faced is regarding pluralism ormust be able to accept every difference that exists. Because as we all know thateach group must have its own unique cultural characteristics or customs, whichcan be said to be difficult or very difficult to understand and influenced by othercultures and groups. Of course, differences in diversity both in terms of religion, ethnicity, culture, language, and nation are certainly something that inevitablymust be accepted together in order to build multiculturalism in order to createjustice, peace, and tolerance.